Relações De Classe, Raça E Políticas Públicas De Expansão Do Ensino Superior No Brasil (2003-2016) - Nogueira, Priscilla Lemos [UNIFESP] (2017)
This Dissertation Aims To Analyze The Expansion Of The Brazilian Higher Education System, Through The Policies That Have Been Carried Out Throughout The Xx Century And Especially The Recent Policies That Look Place Between 2003 And 2016. The Analysis Is Linked To The Inherent Relantionships Of Class Structure And Racial Inequalities That Have Been Perpetuating Within The Society Throughout Its History, And The Quantitative Research Carried Out Through The Profile Data Of Incoming Students At The Federal University Of São Paulo. We Seek To Understand If The Presente Model Of Expasion Presentes Itself As An Ideal Model For Democratization And/Or Diversification Of The Education System, Or Else Perpetuates Public Policies That Benefit The Profitability Of Private Institutions And Segmentation Of Class And Historical Privileges In Public Institutions.